Pengaruh Kepuasan Kerja, Budaya Organisasi dan Komitmen Organisasi Terhadap Kinerja Karyawan - Syardiansah Syardiansah; Zulkarnen Mora; Safriani Safriani (Universitas Negeri Medan, 2020)
This article aims to explain the effect of job satisfaction, organizational culture and organizational commitment on employee performance. The research method uses multiple linear regression analysis. The number of respondents 80 people taken based on the Slovin formula was used as the sample of this study. Based on the analysis results obtained by the linear equation Y = 1.031 + 0.076X1 + 0.368X2 + 0.297X3. From the results of the analysis it was found that the value of the test variable job satisfaction shows a significance value of 0.325> 0.05, then job satisfaction does not have a significant effect on employee performance. Tsig test value of organizational commitment variable shows a significance value of 0.002 <0.05, then organizational commitment has a significant effect on employee performance. And the test value of the organizational culture variable shows a significance value of 0.009 <0.05, the organizational culture has a significant effect on employee performance. Adjusted R Square value of 0.294. This means that the variable Job Satisfaction, Organizational Commitment and Organizational Culture affect Employee Performance at the Cut Meutia Hospital in Langsa City by 0.294 or 29.4%, while the remaining 70.6% It can be concluded that the variables X1, X2 and X3 simultaneously have a significant effect simultaneously on the Y variable. This means that the variables of job satisfaction, organizational commitment and organizational culture together have a significant influence on employee performance